Rare Case of a Chondrosarcoma of the Mandible in a Child. (18th November 2013) - Vieweg, Hendryk; Deichen, Jan Thiess; Scheer, Fabian; Andresen, Reimer; Talanow, Roland
Abstract : Chondrosarcoma of the mandible is rare, especially in children. The available literature consists mostly of a few case reports which are partly integrated in small studies. Growing this small pool of literature is helpful in solidifying knowledge about this disease and facilitating appropriate treatment for children. Therefore, we present such a case in a 12-year-old boy, exhibit comprehensive and relevant information concerning this entity, and discuss our findings in the context of other publications.